Preparation and Performance Evaluation of Novel High Durability Epoxy Asphalt Concrete for Bridge Deck Pavements - Luo, Sang; Qian, Zhendong (Asian Journal of Chemistry, 2014)
In this paper, a novel high durability epoxy asphalt concrete for steel deck pavements is introduced, including the manufacturing process of epoxy asphalt binder and laboratory evaluation for this material.A variety of laboratory tests were conducted to evaluate the pavement performance of the materials, such as Brookfield test, direct tension test, fatigue test, wheel tracking test, moisture susceptibility test and thermal stress restrained specimen test. Test results show that epoxy asphalt binder is a hyperelastic material and epoxy asphalt concrete has 20137 cycles/mm dynamic stability at 70 ºC, 90.8 % tensile strength ratio and -28.4 ºC fracture temperature. The fatigue equations of epoxy asphalt concrete at different temperatures were obtained. It is indicated that the epoxy asphalt concrete is a suitable material for the pavement of long-span steel bridges in China due to its profound performance.